Motif Pengikut Akun Instagram @infodenpasar Untuk Mengunggah Berita Dalam Kegiatan Citizen Journalism - Wira Prananta, Putu Resta; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
The @infodenpasar Instagram account is an account that is part of INFO DENPASAR which aims to provide honest and accurate information in accordance with the journalistic code of ethics, the basic press law and the Electronic Information and Transaction (ITE) law. The purpose of this study is to find out what the motives of @infodenpasar Instagram account’s followers are to upload news in citizen journalism activities. This research uses descriptive quantitative method. The sampling technique used is side purposive technique. The results showed that of the 5 motive indicators, there were only 2 motive indicators that were included in the important category, namely to gain personal and the motive to be involved in the process of disseminating information. These results show that the 2 most important motives that encourage followers of the @infodenpasar Instagram account to upload news are for personal gain and to be involved in information dissemination process. Keywords : Citizen Journalism, Motives, Citizen Journalist, Instagram